PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MATERI SISTEM TATA SURYA UNTUK SISWA SEKOLAH DASAR - Vera Yunita; Mahmud Alpusari; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Android-based learning media is an application that can be accessed and stored on a smartphone by the android operating system. Android can be made by the software aid, one of them is Smart App Creator. Hence, this article discusses the development of android-based learning media for sixth-grade elementary school students. The research is Research and Development with the 4D model. The validation obtained from the validator indicates an average score of 93.75% in the